Pengaruh Dosis Saccharomyces Cerevisiae dan Waktu Fermentasi terhadap Produksi Etanol Bunga Jantan Kelapa Sawit Pasca Anthesis dengan Teknik Immobilisasi - Ratih Rahhutami (Politeknik Kelapa Sawit Citra Widya Edukasi, 2020)
Lignocellulosic materials such as oil palm male flowers can be used as an alternative renewable energy source that is environmentally friendly. The purpose of this study was to determine the potential of oil palm male flowers post anthesis as an alternative raw material for bioethanol using immobilization techniques, determine the best of Saccharomyces cerevisiae dose and fermentation time for ethanol produced and the interactions that occur between the two. This research was conducted at Laboratory of Chemistry Politeknik Kelapa Sawit Citra Widya Edukasi and Laboratory of Biochemistry Institut Pertanian Bogor in April – November 2019. This study used a two factors completely randomized design method. First factor were the dosage of Saccharomyces cerevisiae as much as 25 ml and 50 ml, second factor were the time of fermentation: 2, 3, 4, 5, and 6 days. Each treatments were three replications. The total unit of experiments were 30 unit. Data were analized with analysis of variance with α 5 %, if there was a significant treatment effect, the further analysis using LSD (Least Significant Differences). The results showed that oil palm male flowers post anthesis had the potential to be used as bioethanol with immobilization techniques. The treatment of fermentation time had a significant effect on the ethanol content of oil palm male flowers. However, the dose of Saccharomyces cerevisiae did not significant effect. The best fermentation time was 6 days (17.39%) and there was no interaction between the dose of Saccharomyces cerevisiae and fermentation times to the ethanol content produced.